Fruit seeds and peels – from byproducts to potentially commercial antioxidants - Senawi, Norshazila; Ruzlan, Nurliyana; Koya, Mustapha Suleiman; Syed Osman Idid, Syed Zahir Idid; Mohamed Rehan, Aisyah; Khan Chowdhury, Ahmed Jalal; Kamarudin, Kamarul Rahim (2011)
The aim of this study was to evaluate seeds of guava, papaya and mango for their antioxidant levels and activities (i.e. primary and secondary); and compared antioxidant levels and activities in pulps and peels of two species of dragon fruits, Hylocereus undatus (white dragon fruit) and Hylocereus polyrhizus (red dragon fruit) in order to investigate the possibilities of utilising the selected fruit seeds and peels as commercial nutraceuticals in the future.